PERENCANAAN STRATEGIS PENGEMBANGAN TV KAMPUS ISI SURAKARTA SEBAGAI TELEVISI SENI DAN BUDAYA - Murfianti, Fitri (Acintya, 2014)
This study is an evaluation form of ISI TV. During this time, ISI TV can not be aired optimally but itsexistence is important and necessary either by the campus community and the residents of ISI Surakartaitself. It requires an evaluation to identify the internal and external factors of ISI TV constraints to airperiodically and strategic planning that can be taken to make the ISI TV as an art and culture televisionthat is instructive as well as to be a creative and productive laboratory for lecturers and students.The method used to evaluate this situation is to make the IFE Matrix, EFE Matrix, SWOT Matrix andMatrix QSPM.The results of the study indicate that the campus television ISI TV is internally weak and unresponsiveboth to the opportunities as well as threats that exist in the industry. Therefore, the strategic actionsthat could involve two important aspects include improving management and Rejuvenation Hardware.Reengineering Management is done by optimizing the existing human resources in accordancewith the job description, increasing the number of human resources management in ISI TV, recruitingmore students to join with ISI TV, doing approach to all units in ISI TV, forming curator, working withTV with other cable or local television, building a partnership with the third agent to support thefunding of program activities. Strategic action in rejuvenation equipment is, for example, asking themto help funding in the equipment purchasing to the foreign foundation; and establishing cooperationwith foreign universities also makes the television stations are more advanced technologically.Keywords: Campus TV, Strategic Planning, SWOT